Campak dan Vaksinasi Campak pada Orang Dewasa - Sinto, Robert; Koesnoe, Sukamto; Nelwan, Erni Juwita; Widhani, Alvina; Shakinah, Sharifah; Pasaribu, Adeline; Duindrahajeng, Bernadine Gracia; Suwarto, Suhendro; Nainggolan, Leonard; Chen, Lie Khie; Susilo, Adityo; Maria, Suzy; Hasibuan, Anshari Saifuddin; Wicaksana, Bramantya (UI Scholars Hub, 2026)
Measles is a highly contagious viral infection that remains a significant global health problem despite the availability of an effective vaccine. Measles re-emergence is driven by gaps in immunization coverage, waning post-vaccination immunity, and increased population mobility. In adults, measles infection is associated with greater disease severity compared to children. This literature review was conducted by reviewing recent scientific publications addressing the epidemiology, pathogenesis, clinical manifestations, diagnosis, management, complications, and prevention of measles, with a focus on the adult population. Measles is caused by an RNA virus of the Paramyxoviridae family and is transmitted through respiratory droplets and aerosols. Typical clinical features include fever, cough, coryza, conjunctivitis, and a maculopapular rash with a centrifugal and cephalocaudal distribution. Diagnosis is based on clinical findings and confirmed by laboratory tests such as RT-PCR and measles-specific IgM serology. Measles infection causes significant immunosuppression, including immune amnesia, which increases susceptibility to secondary infections. Management is primarily supportive and vitamin A supplementation has been shown to reduce mortality in certain populations. In adults, complications tend to be more severe, particularly pneumonia as the leading cause of morbidity and mortality, as well as neurological complications such as encephalitis and subacute sclerosing panencephalitis (SSPE). Measles vaccination with the MMR vaccine remains the main prevention strategy. However, its implementation faces challenges, including gaps in immunization coverage, vaccine hesitancy, and limited adult immunization record system. Measles in adults remains a significant health concern with a high risk of severe complication. Strengthening immunization program, improving public education, and developing integrated surveillance system are essential to reduce disease incidence and burden.